Understanding consumer's showrooming behaviour: Extending the theory of planned behaviour. Issue 2 (10th April 2017) - Arora, Sourabh; Singha, Kunal; Sahney, Sangeeta
Abstract : Purpose: Recent multichannel research suggests that consumers use multiple channels to reap attribute-based benefits which have led to showrooming phenomenon. The purpose of this paper is to investigate the reasons for consumers' showrooming behaviour and propose a comprehensive model based on application and extension of the "Theory of planned behaviour". Design/methodology/approach: Using the probability sampling approach, 278 complete responses were obtained via web-based surveys for analysing the showrooming behaviour. The research model was tested using the "Partial least squares method" which follows a variance-based structural equation modelling approach. Findings: The results of the study indicate that "touching and feeling the product" and "sales staff assistance" motivated customers to visit the physical store before buying online. "Better online service quality" and "lower prices online" induced customers to later purchase online. Price conscious customers and those with the ability to use multiple channels were more likely to engage in showrooming behaviour. Research limitations/implications: The generalization of the findings may be limited because the data were collected from a small sample size. The subject calls for more extensive research for drawing generalizations due to lack of the substantive literature on the core area of study. Practical implications: The model proposed will help retailers in understanding the showrooming phenomenon which recent researchers have considered as a threat to retail. The study provides basis for devising strategies to defend showrooming customers. Originality/value: This paper adds to the body of knowledge in retailing by proposing a model on showrooming which is an emerging area of research in the present retail landscape.